Prevalence of Ankylosing Spondylitis Disease Activity Score (ASDAS) inactive disease in a cohort of patients treated with TNF-alpha inhibitors. Issue 3 (4th May 2018) - Monti, Sara; Todoerti, Monica; Codullo, Veronica; Favalli, Ennio Giulio; Biggioggero, Martina; Becciolini, Andrea; Montecucco, Carlomaurizio; Caporali, Roberto
Abstract: Background: Treat to target (T2T), aiming at inactive disease (ID), has become the recommended strategy for axial-SpA (ax-SpA). Using the Ankylosing Spondylitis Disease Activity Score (ASDAS), we assessed the prevalence of ID in ax-SpA patients treated with TNFα inhibitors (TNFi). Methods: A multicentric, cross-sectional study was performed assessing disease activity status (BASDAI and ASDAS) of consecutive patients with ax-SpA on stable treatment with TNFi for at least six months. We analyzed differences with nonradiographic axSpA (nr-ax-SpA) and the influence of population characteristics and comorbidities in reaching ID. ID was defined as ASDAS-CRP <1.3. Results: A total of 218 patients were enrolled, 165 with AS and 53 with nr-ax-SpA. ASDAS-CRP ID was reached by 89 (40.8%) patients, while 163 (74.8%) of patients achieved good disease control with BASDAI. There were no significant differences between the two diagnostic groups. Multivariate logistic regression demonstrated a negative correlation of concomitant fibromyalgia, higher BASMI and current NSAIDs with the chances of reaching ASDAS-CRP ID or BASDAI <4. Conclusion: T2T represents a new challenge in the management of ax-SpA, with recently introduced disease activity measures being significantly more stringent. The prevalence of ID was affected by concomitant fibromyalgia, decreased spine mobility and concomitant NSAIDs.